Myth, ritual, and metallurgy in ancient Greece and recent Africa - Blakely, Sandra. (Cambridge)
xiv, 328 sayfa
Keywords: “In this volume, Sandra Blakely considers technological myths and rituals associated with ancient Greek daimones who made metal and African rituals in which iron plays a central role. Noting the rich semantic web of associations that has connected metallurgy to magic, birth, kingship, autochthony, and territorial possession in both Greek and African cultures, Blakely examines them together in order to cast light on the Greek daimones, which are only fragmentarily preserved and which have often been equated to general types of smithing gods. Her comparison demonstrates that these creatures are more sophisticated and ritually useful, and technology a more nuanced image in Greek myth, than has been previously acknowledged. Using comparative cultural material in a thoughtful and careful way, it helps create a common ground between classical studies and the social science for the study of religion and technology.” --